ANALISA PENGARUH GAYA ELEKTROSTATIK PADA SPEKTRUM PENCITRAAN RESONANSI MAGNETIK (MRI) DALAM JARINGAN BIOLOGI - Salomo Salomo; Nova Lestari; Muhammad Hamdi (Universitas Riau, 2019)
A study of magnetic core resonance imaging modeling of biological tissue has been carried out in analyzing the effect of electrostatic forces with computational approach. This analysis aims to look at the effect of electric and magnetic force on the spectrum of breast cancer tissue. Physical parameters were determined using the modeled wave equation with the application of mathematical wolfram software 9. Computational or modeling results obtained 6 variations of the MRI spectrum showing the peak magnitude of the electric and magnetic spectrum changes by varying the resolution and distance. This is evidenced from the maximum resolution range ie the peak of the electric field spectrum at amplitude 25 a.u is at a concentration of 5 ppm. Resolution of spectrum peak medium is at concentration of 3-4 ppm whereas minimum resolution has 4 peak spectrum that is at concentration 1-2 ppm, 2-3ppm, 3-4ppm and 4ppm. the result of MRI spektrum for distance variation resulted in spectrum change, further reduced the distance then the mri spectrum in magnetic and electric field approaching spin 1.